ANALISIS KEMAMPUAN BERPIKIR LOGIS SISWA DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI BUNYI DI KELAS VIII SMP NEGERI 40 PEKANBARU - Lailatul Badriah; Yennita Yennita; Zuhdi Maaruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to describe the logical thinking ability of VIII grade students of SMP Negeri 40 Pekanbaru by a contextual approach on sound material. The study was conducted from March to april 2018. The subject in this study was 79 students in the two classes have been tested normality and homogeneity. Pre experimental research in the form of intact group comparison was use as the research model. Logical thinking ability test consisting of 15 items of multiple choice option was use as the instrument to obtain the data. Descriptive analisis was used to analize the data and giving a description about the level of logical thinking ability. The logical thinking ability test instrument was developed based on each indicator of logical thinking ability. The data was categorized by the category of logical thinking ability with variable controlling indicators, proporsional reasoning, probabilistic reasoning, correlation reasoning and combinatorial reasoning. Based on the data analysis, the average score of students logical thinking ability in the experimental class was 74,36 which was in in logic category and 62,00 control class which was in quite logic category.Keywords: Contextual approach, Logical Thinking Ability, Logical thinking ability indicator